ANALISIS KEBUTUHAN KEBUGARAN JASMANI UNTUK KESIAPAN BEKERJA PADA SISWA SMK TARUNA KARYA MANDIRI - Daffa Rafid Setiawan; Setio Nugroho; Rekha Ratri Julianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study comprehensively analyzes the physical fitness requirements for work readiness among students at SMK Taruna Karya Mandiri. Work readiness is a critical factor for vocational high school graduates, and physical fitness plays a significant role in enhancing work performance, productivity, and reducing the risk of occupational injuries. Employing a descriptive quantitative research method with a survey approach, supplemented by in-depth interviews, the study gathered data from physical fitness tests administered to students and qualitative insights from key stakeholders including sports teachers, curriculum teachers, industrial relations teachers, and corporate HR representatives. Quantitative results indicate that the distribution of physical fitness levels among students is as follows: 2.00% in